HUBUNGAN KUALITAS BIOLOGI, KIMIA, FISIKA AIR SUMUR DENGAN KEPADATAN PENDUDUK DI KABUPATEN JEMBER - Avishia Prisma Yulivarta; Joko Waluyo; Mochammad Iqbal (Saintifika, 2019)
Biologically, clean water can be said to be suitable for use if the water does not contain pathogenic microorganisms that are harmful to human health. Chemically, consumable water is water that has a pH of 6.5-8.5. Physically it also needs attention. This study aims to find out how the relationship between the quality of biology, chemistry, physics, in Jember Regency well water based on the Republic of Indonesia PERMENKES No.492/MENKES/PER/IV/2010". The research begins with taking samples using purposive sampling technique. Then do the MPN test, acidity test (pH), organoleptic test, TDS test, and dissolved oxygen (DO) test for each sample. Based on the results of the correlation analysis it was found that there was no relationship between biological quality and population density and there was a relationship between the quality of physics and population density and there was no relationship between chemical quality (pH) but between chemical qualities (DO) with population density there is a relationship.